Factors propelling the adoption of internet banking: the role of e-customer service, website design, brand image and customer satisfaction. (10th March 2020) - Rahi, Samar; Ghani, Mazuri Abd; Ngah, Abdul Hafaz
In recent years, technology adoption has been seen as a critical and distinct topic in e-commerce research. Looking at the challenges in technology adoption faced by banking sector of Pakistan, this study examined the effect of website design, customer service and brand image on customer's intention to adopt internet banking. Additionally, customer satisfaction is integrated in theoretical framework as a mediating variable. The data for this study was collected from internet banking users. Structural equation modelling (SEM) has employed to evaluate the hypothesised relationships. The results of this study revealed that the adoption of internet banking in Pakistan is motivated by a set of specific factors (i.e., website design, e-customer service, customer satisfaction and brand image). Practically, these results will help policy makers to understand critical factors that influence on customer's intention to adopt internet banking in Pakistan. Finally, limitations and future research directions have been discussed.